Physical growth in twins, postmature and small-for-dates children. Issue 6 (June 1975) - Chamberlain, R; Davey, A
Abstract : From 16 955 livebirths, which occurred throughout the United Kingdom in April 1970 during the British Births Survey, three groups of children (multiple births, postmature, and small-for-dates) were selected together with a 10% random sample. This report is concerned with the height, weight, and head circimference measruements at 22 months of age. The babies that were heavier at birth showed diminished growth velocity and the small babies catch-up growth. At 22 months the pattern of distribution of weight was much closer to the normal than that of the babies' birthweights. Differences, however, did remain.